Tolak Balak Local Traditions of Sea Rituals in the Sabu Tribe of East Nusa Tenggara in the Midst of Modern Culture - Mustolehudin, Mustolehudin; Hamid, Wardiah; Dachlan, Muhammad; Israpil, Israpil (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2025)
The Tolak Balak ritual is an important tradition performed by the Sabu tribe in East Nusa Tenggara to ask for protection and safety from evil spirits. This ritual has been going on for a long time and is an important part of the Jingitiu religious beliefs. However, the impact of modernization has caused some major difficulties. This article looks at how the Tolak Balak ritual is adapting to the rapidly evolving social, cultural, and technological changes in Sabu society. Although modernization and technological advances make it easy, they also affect the way this tradition is performed and how the younger generation perceives it. This study shows that Savunese people can maintain the essence and meaning of the Tolak Balak ritual by changing and updating its implementation even though the changing times are destroying it. In addition, the article links this tradition to broader conversations about the preservation of local cultural heritage amidst modernization and globalization. This article provides insight into the importance of the Tolak Balak tradition for the people of Savu and shows how local traditions can survive and thrive in the face of today's challenges.